PERLAKUAN PERPAJAKAN DI SEKTOR PERTAMBANGAN PANAS BUMI (GEOTHERMAL) - Louisa Maria I.M. (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Geothermal is an alternative form if energy that we can depend on for today and the future, as well as a solution to solve the scarcity of electricity in Indonesia. Unfortunately, the geothermal industry in our country is confronted with a lot obstacles, technically and non-technically as well, as a result this industry has a difficulty to grow. Geothermal is one of the primary energy that can be renewed (renewable resources) and environmental friendly(Green Energy) and it can also be used as a source of electric energy. Geothermal is said to be environmental friendly because it is clean (doesn’t contain CO2) and other element that are found in geothermal do not produce any consequences to environment. According to Law No.27 in 2003 about geothermal (which is called The Law of Geothermal), the definition of geothermal is: “A source of heat energy that is contained inside hot water, water vapor and rocks, as well as of the minerals and other gases that cannot be separated from geothermal genetically and a mining process is requires for its utilization